CRP-cyclic AMP dependent inhibition of the xylene-responsive σ(54)-promoter Pu in Escherichia coli. - Yuan-Tao Zhang (Public Library of Science (PLoS), 2014)
The expression of σ(54)-dependent Pseudomonas putida Pu promoter is activated by XylR activator when cells are exposed to a variety of aromatic inducers. In this study, the transcriptional activation of the P. putida Pu promoter was recreated in the heterologous host Escherichia coli. Here we show that the cAMP receptor protein (CRP), a well-known carbon utilization regulator, had an inhibitory effect on the expression of Pu promoter in a cAMP-dependent manner. The inhibitory effect was not activator specific. In vivo KMnO4 and DMS footprinting analysis indicated that CRP-cAMP poised the RNA polymerase at Pu promoter, inhibiting the isomerization step of the transcription initiation even in the presence of an activator. Therefore, the presence of PTS-sugar, which eliminates cAMP, could activate the poised RNA polymerase at Pu promoter to transcribe. Moreover, the activation region 1 (AR1) of CRP, which interacts directly with the αCTD (C-terminal domain of α-subunit) of RNA polymerase, was found essential for the CRP-mediated inhibition at Pu promoter. A model for the above observations is discussed.